An Adjoint Sensitivity Method Applied to Time Reverse Imaging of Tsunami Source for the 2009 Samoa Earthquake. Issue 2 (17th January 2018) - Hossen, M. Jakir; Gusman, Aditya; Satake, Kenji; Cummins, Phil R.
Abstract: We have previously developed a tsunami source inversion method based on "Time Reverse Imaging" and demonstrated that it is computationally very efficient and has the ability to reproduce the tsunami source model with good accuracy using tsunami data of the 2011 Tohoku earthquake tsunami. In this paper, we implemented this approach in the 2009 Samoa earthquake tsunami triggered by a doublet earthquake consisting of both normal and thrust faulting. Our result showed that the method is quite capable of recovering the source model associated with normal and thrust faulting. We found that the inversion result is highly sensitive to some stations that must be removed from the inversion. We applied an adjoint sensitivity method to find the optimal set of stations in order to estimate a realistic source model. We found that the inversion result is improved significantly once the optimal set of stations is used. In addition, from the reconstructed source model we estimated the slip distribution of the fault from which we successfully determined the dipping orientation of the fault plane for the normal fault earthquake. Our result suggests that the fault plane dip toward the northeast. Key Points: The Green's Function based Time Reverse Imaging method is implemented in the 2009 Samoa tsunami triggered by a doublet earthquake An adjoint sensitivity method is applied to find the optimal set of stations for tsunami source inversion Results show that the GFTRI with adjoint method is able to recover the tsunami source associated with both normal and thrust faultings